2017
DOI: 10.1111/nep.12852
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between subclinical hypothyroidism and renal function in patients with diabetes mellitus

Abstract: These findings demonstrate an association of SCH with renal injury in diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Previous studies reported that both hypothyroidism and hyperthyroidism worsen kidney function directly by affecting renal blood flow, GFR, tubular function, electrolyte homeostasis, electrolyte pump functions, and kidney structure (e.g., decreased glomerular volume and area) and increasing peripheral vascular resistance [14][15][16], leading to higher serum CR concentrations and a lower eGFR. Several researchers also found an association of subclinical hypothyroidism with renal injury, such as macroalbuminuria in DM subjects [32][33][34][35]. Similarly, in our current study, the prevalence of these three kidney disorders was significantly different when all participants were grouped by the reference range of TSH, the distribution of which looked like a "U" shape.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies reported that both hypothyroidism and hyperthyroidism worsen kidney function directly by affecting renal blood flow, GFR, tubular function, electrolyte homeostasis, electrolyte pump functions, and kidney structure (e.g., decreased glomerular volume and area) and increasing peripheral vascular resistance [14][15][16], leading to higher serum CR concentrations and a lower eGFR. Several researchers also found an association of subclinical hypothyroidism with renal injury, such as macroalbuminuria in DM subjects [32][33][34][35]. Similarly, in our current study, the prevalence of these three kidney disorders was significantly different when all participants were grouped by the reference range of TSH, the distribution of which looked like a "U" shape.…”
Section: Discussionsupporting
confidence: 80%
“…Cr clearance (Ccr) and urinary albumin excretion rate (UAER) were calculated as previously. 50 All measurements were done in duplicate for n = 10 rats/group.…”
Section: Biochemical Analysismentioning
confidence: 99%
“…P rimary hypothyroidism is characterized by a high concentration of thyrotropin (TSH) concomitant with concentrations of thyroid hormones being low (overt) or within the reference range (subclinical). In conventional nongenetic observational studies, both overt and subclinical hypothyroidism are associated with increased plasma creatinine, decreased estimated glomerular filtration rate (eGFR), chronic kidney disease (CKD), and increased urinary albumin/creatinine ratio (UACR) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Overt hypothyroidism is most often an autoimmune disease in adults, (13) affecting predominantly middle-aged and older women.…”
Section: Introductionmentioning
confidence: 99%